Análise espaço-temporal da ocorrência da malária para avaliação da dinâmica de transmissão no município de Colniza/MT, no período de 2003 à 2009 - Araujo, Valdenir Santana (2013)
Malaria is a disease caused by the protozoa, febrile genus Plasmodium transmitted by vectors of the genus Anopheles, especially Anopheles darlingi in Brazil. Negative influences disease on socioeconomic development and on quality of life of the local population is considered endemic in the municipality of Colniza, located in the extreme Northwest, part of the Amazon state of Mato Grosso, showing higher incidence. In this context, we analyzed the spatio-temporal distribution of the occurrence of malaria in the municipality of Colniza for determining the transmission dynamics of the disease, to which the geographic information system (GIS) in the period from 2003 to 2009, being developed based on secondary data records bailiffs malaria cases in Legal Amazon, obtained from Epidemiological Surveillance Information System – (SIVEP-Malaria). For spatialization of the occurrence of cases in the city, it was necessary to construct a Cartographic base of Colniza with identification of localities in which there have been records of the disease during the period surveyed, as well as the use of satellite images to verify the possible interaction of the dynamics of deforestation and the occurrence of malaria. The rates of occurrence of malaria were calculated through the Empirical Bayesian Model Global that estimates the rate to localities considering the values of localities within a determined, taking into consideration the values of cases and number of inhabitants of the localities within that radius. The use of this technique decreases the random fluctuation that occurs due to differences in cases in other locales. Over the period researched 21.417 malaria cases occurred in Colniza, it was found that the largest number of cases of the disease had the cause of infection by Plasmodium vivax, registering a total of 16.187 cases. The districts who have excelled in number of cases of the disease were Guariba (locale Triunfo) and Três Fronteiras (locale Mineração São Francisco - Três Fronteiras). In the year of 2007 there was a significant increase of recorded a significant increase of 663.77% in Mineração São Francisco the number of cases in the previous year. The biggest cases of malaria were reported in towns whose economic activities mining, gold prospecting and farming. Mineração São Francisco - Três Fronteiras location in the District of Três Fronteiras recorded the two highest rates of malaria infection to laughter in the year of 2008 and 2009, the second location to score highest rate was the riverside locale Novo Mundo II Rio Roosevelt in the year 2009. In risk areas maps pointed to by IPA calculated by Bayesian Estimator, pointed out locations that did not provide numbers of absolute high, but that cases on the average of the calculated rate, shown as high-risk areas to contract the disease.